Performance analysis of a dual stage deep rain streak removal convolution neural network module with a modified deep residual dense network - Jayaraman, Thiyagarajan; Chinnusamy, Gowri Shankar (Zielona Góra: Uniwersytet Zielonogórski)
The visual appearance of outdoor captured images is affected by various weather conditions, such as rain patterns, haze, fog and snow. The rain pattern creates more degradation in the visual quality of the image due to its physical structure compared with other weather conditions. Also, the rain pattern affects both foreground and background image information. The removal of rain patterns from a single image is a critical process, and more attention is given to remove the structural rain pattern from real-time rain images.
Keywords: single image deraining; deep learning; modified residual dense network; PyTorch